(untitled) (Journal of Health Sciences, 2016)
Ectopic decidua is defined as extrauterine deposits of decidual stromal cells. It occurs in 85-100% of pregnancies. Focal sites can be present in various locations, yet a peritoneal location is rare. A 24- year- old woman underwent a cesarean section in 39th week of her first pregnancy, during which adhesions of the omentum to the fundus, entire left side of the uterus, and a part of the right front abdominal wall were found. An operative specimen was taken for a pathohistological analysis under the assumption of being fibrous adhesive tissue. The analysis revealed ectopic decidual tissue composed of large, polygonal cells with eosinophilic cytoplasm, and large nuclei with conspicuous nucleoli infiltrated with mature fatty cells and lymphocytes. Strong staining for vimentin was observed in the decidual cell cytoplasm and for a progesterone- receptor in the cell nuclei, medium staining was detected for S-100, and negative staining for CK 5/ 6, HMB-45, desmin, smooth muscle actin, estrogen and androgen- receptors. We present this case in order to educate clinicians and pathologists about the phenomenon of ectopic deciduosis. Although it can exist as asymptomatic condition, we point out the importance of considering this condition since it can result in serious pathology, like intraperitoneal hemorrhage and labour obstruction, if remains unrecognized. Another pitfall is possible confusion of this entity with other conditions. A resemblance to adhesions of the omentum and malignant neoplastic lesions, like squamous cell and metastatic carcinoma, metastatic melanoma, malignant decidual mesothelioma, metastatic mucin -producing adenocarcinoma, can be deceiving. These obstacles may present a pitfall to clinicians and pathologists, with a negative impact on patient treatment and outcome.